Integration of Kansei Engineering and Design Thinking for Mobile UI/UX Development in Manufacturing - Izzuddin, Adam; Suzianti, Amalia (Universitas Airlangga, 2025)
The increasing digitalization of the manufacturing industry has encouraged companies to develop mobile applications that can optimize operational and administrative processes. However, limited studies have specifically addressed integrating emotional and functional aspects in designing user interfaces (UI) and user experiences (UX) for mobile applications in the manufacturing context. This study aims to develop a mobile application UI/UX design that aligns with users' emotional preferences and usability needs across three departments: logistics, maintenance, and production. The research integrates the Kansei Engineering method and Design Thinking framework through five stages: empathize, define, ideate, prototype, and test. In the empathize stage, in-depth interviews and empathy mapping were conducted to capture user needs, utilizing a qualitative approach to gain deep insights into users’ emotional preferences. The ideate phase utilized Kansei Engineering Type I and factor analysis to classify emotional preferences (Kansei words) into two design modes: professional and simple. Quantitative analysis using Partial Least Squares (PLS) Regression was applied to map emotional preferences with design elements. Prototypes were developed based on these mappings and evaluated through usability testing, using metrics such as completion rate, time on task, error rate, and PSSUQ (Post-Study System Usability Questionnaire). The results show that the professional concept design performed better in usability and user satisfaction. This research provides a practical framework for integrating emotional and functional needs into UI/UX design, combining qualitative and quantitative methods, and offers insights for future digital application development in the manufacturing industry.